2004
DOI: 10.3141/1897-05
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Ranking of Black Spots: Sensitivity Analysis

Abstract: In Flanders, Belgium, approximately 1,014 accident locations are considered dangerous. These dangerous accident sites, or black spots, are selected by means of historic accident records for the period 1997 to 1999. A combination of weighting values, respectively, 1 for each light injury, 3 for each serious injury, and 5 for each deadly injury (1_3_5), is used to rank and select the most dangerous accident locations. A sensitivity analysis was performed to investigate the effect on the identification and rankin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(38 citation statements)
references
References 12 publications
0
34
0
1
Order By: Relevance
“…In accordance with our previous research (Geurts et al, 2004), we will use the percentage deviation value to quantify the effects changing the ranking and selection criteria of dangerous accident locations. This measure allows comparing the rankings of two datasets containing different locations.…”
Section: Percentage Deviation Valuementioning
confidence: 99%
See 4 more Smart Citations
“…In accordance with our previous research (Geurts et al, 2004), we will use the percentage deviation value to quantify the effects changing the ranking and selection criteria of dangerous accident locations. This measure allows comparing the rankings of two datasets containing different locations.…”
Section: Percentage Deviation Valuementioning
confidence: 99%
“…One of the advantages of this MCMC method is that it allows for exploring posterior distributions of a certain function related to the parameters of interest. Results (Geurts et al, 2004) showed that the use of these Bayesian estimation values from this model instead of historic count data to rank the accident locations indeed can overcome the problem of random variation in accident counts and will have an important effect on the selection of the most dangerous accident locations.…”
Section: Bayesian Ranking Plotmentioning
confidence: 99%
See 3 more Smart Citations